HR+HER2− breast cancers with growth factor receptor–mediated EMT have a poor prognosis and lapatinib downregulates EMT in MCF-7 cells. Issue 3 (March 2017) - Desai, Krisha; Aiyappa, Radhika; Prabhu, Jyothi S; Nair, Madhumathy G; Lawrence, Patrick Varun; Korlimarla, Aruna; CE, Anupama; Alexander, Annie; Kaluve, Rohini S; Manjunath, Suraj; Correa, Marjorrie; Srinath, BS; et al.
Despite an overall good prognosis, a significant proportion of patients with hormone receptor positive human epidermal growth factor receptor 2 negative breast cancers develop distant metastases. The metastatic potential of epithelial cells is known to be regulated by tumor–stromal interaction and mediated by epithelial-to-mesenchymal transition. Hormone receptor positive human epidermal growth factor receptor 2 negative tumors were used to estimate markers of epithelial-to-mesenchymal transition, and the luminal breast cancer cell line MCF-7 was used to examine the interactions between integrins and growth factor receptors in causation of epithelial-to-mesenchymal transition. A total of 140 primary tumors were sub-divided into groups enriched for the markers of epithelial-to-mesenchymal transition (snail family transcriptional repressor 2 and integrin β6) versus those with low levels. Within the epithelial-to-mesenchymal transition+ tumors, there was a positive correlation between the transcripts of integrin β6 and growth factor receptors—human epidermal growth factor receptor 2 and epidermal growth factor receptor. In tumors enriched for epithelial-to-mesenchymal transition markers, patients with tumors with the highest quartile of growth factor receptor transcripts had a shorter disease-free survival compared to patients with low growth factor receptor expression by Kaplan–Meier analysis (log rank, p = 0.03). Epithelial-to-mesenchymal transition was induced in MCF-7 cells by treatment with transforming growth factor beta 1 and confirmed by upregulation of SNAI1 and SNAI2 transcripts, increase of vimentin and integrin β6 protein, and repression of E-cadherin. Treatment of these cells with the dual-specificity tyrosine-kinase inhibitor lapatinib led to downregulation of epithelial-to-mesenchymal transition as indicated by lower levels of SNAI1 and SNAI2 transcripts, integrin αvβ6, and matrix metalloproteinase 9 protein. The results suggest that synergistic interactions between growth factor receptors and integrin β6 could mediate epithelial-to-mesenchymal transition and migration in a subset of luminal breast cancers and lapatinib might be effective in disrupting this interaction.